Implementation of cleanliness, health, safety and environment sustainable (CHSE) in the new normal era in tourism attraction in West Bandung district West Java - Erie Hidayat Sukriadi; Rachmat Astiana (Universitas Merdeka Malang, 2022)
The tourism industry is one of the sectors that has been affected by the COVID-19 pandemic. Because it is the earliest to be affected, the highest risk of loss, and the last to recover. So that West Java Province, especially West Bandung Regency which has natural, cultural, and artificial tourist destinations also experienced the impact of decreasing the number of tourist visits even though the contribution of the tourism sector to locally-generated revenue (PAD) is quite large every year. to implement the Cleanliness, Health, Safety, Environmental Sustainable (CHSE) Protocol in various fields, one of which is tourist attractions. This study aims to determine the application of the CHSE protocol in the tourist attraction of West Bandung Regency with data collection techniques through field observations and conducting interviews with tourist attraction managers and processing them using qualitative methods. The results of the study are that the application of CHSE in tourist attractions has been carried out well, although there are few notes to further improve its services.